Characteristics of Impactites in the Central Uplift of the Mistastin Lake Impact Structure, Canada - Singleton, Alaura (Scholarship@Western, 2019)
This thesis investigated the nature of parautochthonous and allochthonous impactites found in the erosional remnant of the central uplift of the Mistastin Lake impact structure, central Labrador. This was carried out with the goal of discovering details about the composition and formation conditions of these complex materials. This study involved fieldwork and a range of laboratory techniques. As part of this work, a geological map of Horseshoe Island has been created, and is the most detailed to date. The shock metamorphic features found in the uplifted target rocks have been assessed, and indicate a peak shock level of 5a (35-45 GPa). The erosion of the central uplift has been shown to be minimal; both through the observation of remnant impact melt on the island, and the shock features present. Field and microscopy observations suggest that impact breccias found on Horseshoe Island were dynamically emplaced into the surrounding target rocks. Small glass clasts found in the impact melt-bearing breccia, and impact melt rock from Horseshoe Island, are found to be derived predominantly from quartz monzonite with lesser anorthosite, giving this melt material a composition unique from other melts previously studied at the Mistastin structure. These results provide insight into the initial stratigraphy of the target area, indicating a body of quartz monzonite found stratigraphically below the anorthosite, and, in addition, demonstrates that the composition of the melts created by this impact event are more variable than previously thought. Detailed chemical mapping of the glass clasts has revealed their complex nature. The lithic fragments found entrained in the glass are derived from both quartz monzonite and anorthosite, and the concentrations of siderophile elements indicate a strong likelihood of a meteoritic component. The oxidation state of iron in two melt clasts was examined, and indicates that these melts have their origin as part of the melt sheet. This investigation into the nature, diversity and ...